Capital structure decision: micro- and macroeconomic determinants in Malaysia - Julkid, Noor Farahanim; Lau, Wei Theng (Human Resource Management Academic Research Society, 2020)
This paper attempts to analyse the determinants of capital structure decisions among Malaysian firms by considering both the firm-specific (micro-economic) and the macro-economic factors. Using a sample covering 612 listed firms across major business sectors in the Bursa Malaysia during a span of ten recent years (2009-2018), the analysis proposes that both the micro- and macro-economic determinants are relevant for decision makers in understanding the financial leverage of firms. Panel data regressions suggest a significant positive relationship of non-debt tax shield, firm size, tangibility, interest rate and stock market development with debt ratio of firms. Meanwhile, a significant negative relationship is found for profitability, liquidity and gross domestic product. While the macro-economic variables are proposed to be fundamentally important in this study, they do not affect the roles of commonly proposed firm-specific factors implied by the existing capital structure theories. The results are also robust across the estimations with pooled ordinary least squares, fixed effects and random effects models. This paper particularly focuses on providing empirical evidence from the Malaysian market, extendable to cover the other countries for future investigations.